Rating Nasolabial Aesthetics in Unilateral Cleft Lip and Palate Patients: Cropped Versus Full-Face Images. (May 2018) - Schwirtz, Roderic M. F.; Mulder, Frans J.; Mosmuller, David G. M.; Tan, Robin A.; Maal, Thomas J.; Prahl, Charlotte; de Vet, Henrica C. W.; Don Griot, J. Peter W.
Objective: To determine if cropping facial images affects nasolabial aesthetics assessments in unilateral cleft lip patients and to evaluate the effect of facial attractiveness on nasolabial evaluation. Design: Two cleft surgeons and one cleft orthodontist assessed standardized frontal photographs 4 times; nasolabial aesthetics were rated on cropped and full-face images using the Cleft Aesthetic Rating Scale, and total facial attractiveness was rated on full-face images with and without the nasolabial area blurred using a 5-point Likert scale. Setting: Cleft Palate Craniofacial Unit of a University Medical Center. Patients: Inclusion criteria: nonsyndromic unilateral cleft lip and an available frontal view photograph around 10 years of age. Exclusion criteria: a history of facial trauma and an incomplete cleft. Eighty-one photographs were available for assessment. Main Outcome Measures: Differences in mean CARS scores between cropped versus full-face photographs and attractive versus unattractive rated patients were evaluated by paired t test. Results: Nasolabial aesthetics are scored more negatively on full-face photographs compared to cropped photographs, regardless of facial attractiveness. (Mean CARS score, nose: cropped = 2.8, full-face = 3.0, P < .001; lip: cropped = 2.4, full-face = 2.7, P < .001; nose and lip: cropped = 2.6, full-face = 2.8, P < .001). Conclusion: Aesthetic outcomes of the nasolabial area are assessed significantly more positively when using cropped images compared to full-face images. For this reason, cropping images, revealing the nasolabial area only, is recommended for aesthetical assessments.